2020
DOI: 10.1002/ajmg.a.62027
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cerebral and coronary aneurysms in the original two patients with Kosaki overgrowth syndrome

Abstract: Skeletal overgrowth accompanied by de novo heterozygous activating mutations in PDGFRB (platelet‐derived growth factor receptor beta), that is, p.Pro584Arg and p.Trp566Arg, defines Kosaki overgrowth syndrome (OMIM #616592). Emerging evidence suggests a role of PDGFRB in the genesis of cerebral aneurysms. The delineation of the range and progression of the vascular phenotype of Kosaki overgrowth syndrome is urgently needed. Herein, we conducted subsequent analyses of serial neurovascular imaging studies of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Western blot analysis has shown that expression of the Tyr562Cys variant is consistent with higher basal levels of pPDGFRB, pSRC, pAKT, and pERK1/2, and PDGFRB phosphorylation can activate downstream signaling ( 26 ). PDGFRB phosphorylation contributed to cerebrovascular dilation and lesions, which is observed to be expressed in vascular smooth muscle cells ( 341 ). More recently, the individual with intracranial aneurysm was observed to have PDGFRB alteration, where the vascular complications like SAH may be associated with PDGFRB hyperactivation ( 342 , 343 ).…”
Section: Multiple Treatment Strategies For Sahmentioning
confidence: 99%
“…Western blot analysis has shown that expression of the Tyr562Cys variant is consistent with higher basal levels of pPDGFRB, pSRC, pAKT, and pERK1/2, and PDGFRB phosphorylation can activate downstream signaling ( 26 ). PDGFRB phosphorylation contributed to cerebrovascular dilation and lesions, which is observed to be expressed in vascular smooth muscle cells ( 341 ). More recently, the individual with intracranial aneurysm was observed to have PDGFRB alteration, where the vascular complications like SAH may be associated with PDGFRB hyperactivation ( 342 , 343 ).…”
Section: Multiple Treatment Strategies For Sahmentioning
confidence: 99%